Possibility of Pantyhose Design Using Clothing Pressure and Myoelectric Potential as Indices (Journal of Fiber Bioengineering and Informatics, 2023)
This paper reports a study of 13 Japanese women who wore two types of pantyhose that were ratedas providing an “almost-perfect pressure sensation” and three types of shoes. The root mean squareof the electromyogram for eight muscles in the right leg was calculated. RMS has divided four groupmuscles: into each muscle around the knee, around the knee, on the ventral side, and on the dorsal side,and investigated how it changes between bare feet, pantyhose, and shoes. Each pantyhose is designedto stretch the legs well and follow the walking motion easily, but pantyhose B is double woven fromthe abdomen to the backside so as to connect to the back side while lifting the subcutaneous fat of theabdomen. Even if the pantyhose is made to apply almost the same pressure to the ankles, changing thedesign of the panty part can activate or suppress abdominal muscle activity.